Ultrathin all-2D lateral graphene/GaS/graphene UV photodetectors by direct CVD growth - Chen, T; Lu, Y; Sheng, Y; Shu, Y; Li, X; Chang, R-J; Bhaskaran, H; Warner, JH (American Chemical Society, 2019)
UV-sensitive lateral all-two-dimensional (2D) photodetecting devices are produced by growing the large band gap layered GaS between graphene electrode pairs directly using chemical vapor deposition methods. The use of prepatterned graphene electrode pairs on the Si wafer enables more than 200 devices to be fabricated simultaneously. We show that the surface chemistry of the substrate during GaS leads to selective growth in graphene gaps, forming the lateral heterostructures, rather than on the surface of graphene. The graphene/GaS/graphene lateral photodetecting devices are demonstrated to be sensitive to UV light only, with no measurable response to visible light. Furthermore, we demonstrate UV-band discrimination in photosensing, with measured photocurrents only produced for middle-UV and not for near-UV wavelength regions. The detection limit could reach down to 2.61 μW/cm2 with a photoresponsivity as high as 11.7 A/W and a photo gain of 53.7 under 270 nm excitation. Gate-dependent modulation of the photocurrent is also demonstrated. The photodetectors exhibit long-term stability and reproducible ON-OFF switching behavior, with a response time lower than 60 ms. These results provide insights into how ultrathin UV sensing devices can be created using only 2D materials by exploiting large band gap 2D semiconductors such as GaS.